Three Inulin-Type Fructans from Codonopsis pilosula (Franch.) Nannf. Roots and Their Prebiotic Activity on Bifidobacterium longum - Jiankuan Li (Molecules, 2018)
Radix Codonopsis, derived from the roots of Codonopsis pilosula (Franch.) Nannf., Codonopsis pilosula (Franch.) Nannf. Var. modesta (Nannf.) L.T. Shen and Codonopsis tangshen Oliv., has been used as traditional Chinese medicine for improving poor gastrointestinal function, treating gastric ulcers and chronic gastritis in China. Inulin-type fructans are carbohydrates consisting mainly of β (2→1) fructosyl-fructose links in chemical structure and exhibit a range of properties such as prebiotic activity, fat substitutes in low-calorie foods and disease-modifying effects. The prebiotic effects of inulin-type fructans are hypothesized to improve gastrointestinal function through alterations to gut microbiota composition and metabolism. In the present study, three inulin-type fructans with high degree of polymerization (DP = 16, 22, and 31) were isolated from the roots of Codonopsis pilosula (Franch.) Nannf. and their structures were confirmed by MALDI-TOF-MS, 1D- and 2D-NMR. The prebiotic activity of these fructans was evaluated by detecting growth stimulation on Bifidobacterium longum. The results demonstrated that three fructans at a concentration of 2.0 g/L exhibited significant growth stimulation on Bifidobacterium longum in a time-dependent manner (p < 0.01). The data indicated that inulin-type fructans in Radix Codonopsis could be used as potential prebiotics.